2023
DOI: 10.1007/s00383-023-05448-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome, quality of life, and mental health in long-gap esophageal atresia: comparison of gastric sleeve pull-up and delayed primary anastomosis

Abstract: Introduction Pediatric surgeons have yet to reach a consensus whether a gastric sleeve pull-up or delayed primary anastomosis for the treatment of esophageal atresia (EA), especially of the long-gap type (LGEA) should be performed. Thus, the aim of this study was to evaluate clinical outcome, quality of life (QoL), and mental health of patients with EA and their parents. Methods Clinical outcomes of all children treated with EA from 2007 to 2021 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Out of 345 articles identified by the database searches, 49 articles met the inclusion criteria. 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 Most concerned esophageal atresia ( n = 17) and Hirschsprung's disease ( n = 14). None of the articles focused on duodenal atresia or omphalocele.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 345 articles identified by the database searches, 49 articles met the inclusion criteria. 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 Most concerned esophageal atresia ( n = 17) and Hirschsprung's disease ( n = 14). None of the articles focused on duodenal atresia or omphalocele.…”
Section: Resultsmentioning
confidence: 99%
“…A study of healthrelated quality of life in children and adolescents with spina bifida showed that there was no difference in health-related quality of life between patients and healthy children and adolescents [16]. Also, in the quality-of-life surveys of patients with esophageal atresia [11,12], asthma and type 1 diabetes [5,17], heart defects [18], cancer [19], or hereditary diseases such as Marfan syndrome [20], it was found that the diseases do not necessarily result in a poorer quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most commonly used instruments for children are the Child Health and Illness Profile (CHIP) [8], the KIDSCREEN-52 [9], the KINDL [5], the Pediatric Quality of Life Inventory (PedsQL) [10][11][12], and the DISABKIDS [13,14]. For our study, we chose the KINDL R questionnaire, which is a measure of HRQoL in healthy and ill children and adolescents (aged 3 years and older) and has been rated as a good and reliable questionnaire.…”
Section: Assessment Of Quality Of Life With the Kindl Questionnairementioning
confidence: 99%